Energy efficiency as a development tool of a modern higher education institution - Okushko, O.; Radko, I.; Nalyvaiko, V. (Energy and Automation, 2023)
The article presents new scientific results of experimental research, which relate to the analysis of low energy efficiency of urban residential and communal heat supply, using the example of higher education institutions. The purpose of the study is to reduce heating costs in public and educational and industrial buildings of higher education institutions Based on the analysis of the state of energy efficiency in the housing and communal economy, a number of main factors influencing the reduction of energy efficiency have been established. Among the main ones that require research, we can single out, first of all, insufficient attention to stimulating energy efficiency issues, outdated equipment and low qualification of service personnel Based on the results of the research, the priority directions for reducing heat losses were determined and the heating system is being studied by improving the thermophysical characteristics of the enclosing structures of buildings, introducing heat screens for radiators, and finally, developing and implementing automated systems for registration and monitoring of the flow of coolant to heat points. The obtained research results are of important practical importance in the development of a systemic, state approach and the development of organizational and economic recommendations for improving the quality of energy supply, energy saving and energy efficiency. Energy-saving measures are proposed, which will contribute to increasing the efficiency of production activities of enterprises, where up to 35-40% of energy resources are lost due to the wear and tear of operational equipment. Key words: energy consumption, system, management, energy resources, funds, losses, savings, energy carrier, electric energy, thermal energy